2020
DOI: 10.37506/ijfmt.v14i2.3229
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Parenting Styles and Peer Attachment with Aggressive Behavior Potentials in Adolescent Boys

Abstract: Background: Adolescence is a transitional phase that causes biological, cognitive, social-emotional, and behavioral changes. One of the issues of concern is aggressive behavior in adolescents. Parenting styles and peer attachment are one of the factors that have an influence on potential aggressive behavior in adolescent boys.Objectives To analyze the relationship between parenting styles and peer attachment to the potential aggressive behavior of adolescent boys. Method:The subjects were junior high school ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
(15 reference statements)
1
3
0
Order By: Relevance
“…Similarly, the finding is corroborated by the findings of Masud et al (2019), who found that aggression could be linked with parenting styles in both negative and positive ways. However, the finding partially agrees with the findings of Setiawati et al (2020), who reported a positive but nonsignificant relationship between parental styles and aggressive behavior in teenage boys. This contrast may stem from the biased sample of their study “teenage boys.” This present study sampled both male and female teenagers.…”
Section: Discussion Of Findingssupporting
confidence: 91%
See 2 more Smart Citations
“…Similarly, the finding is corroborated by the findings of Masud et al (2019), who found that aggression could be linked with parenting styles in both negative and positive ways. However, the finding partially agrees with the findings of Setiawati et al (2020), who reported a positive but nonsignificant relationship between parental styles and aggressive behavior in teenage boys. This contrast may stem from the biased sample of their study “teenage boys.” This present study sampled both male and female teenagers.…”
Section: Discussion Of Findingssupporting
confidence: 91%
“…The impact of peer pressure and parenting styles on the aggressive behavior of teenage boys was studied by Setiawati et al in 2020. The findings showed a relationship between parental styles and aggressive behavior in teenage boys that were positive but not statistically significant; the relationship between aggressive behavior and peer influence was negative but statistically significant.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The parenting style of parents who are doing their role poorly and the lack of positive parenting practices will be a risk factor for the onset of ADHD in children ( 2 ). Parents who often give threats or punishments to their children will be a different risk factor for the emergence of the aggressive nature of the child ( 21 ). Authoritarian parenting is a type of parenting that should not be applied by parents where the impact of the child being less attention from parents in parenting will reduce cognitive stimulation in children ( 22 ).…”
Section: Discussionmentioning
confidence: 99%